2012
DOI: 10.1111/j.1365-2966.2012.21312.x
|View full text |Cite
|
Sign up to set email alerts
|

Baroclinic instability on hot extrasolar planets

Abstract: We investigate baroclinic instability in flow conditions relevant to hot extrasolar planets. The instability is important for transporting and mixing heat, as well as for influencing largescale variability on the planets. Both linear normal mode analysis and non-linear initial-value calculations are carried out -focusing on the freely-evolving, adiabatic situation. Using a highresolution general circulation model (GCM) which solves the traditional primitive equations, we show that large-scale jets similar to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 49 publications
6
48
0
Order By: Relevance
“…This is even more so for finite-volume codes such as RAMSES that have problems handling hydrostatic equilibria, and we found that problem to be very helpful in assessing the reliability of our setup. In this appendix, we thus qualitatively reproduce one of the models presented by Polichtchouk & Cho (2012), namely their equatorial jet case, since the base flow is close to the jet configuration we studied here. As noted by Polichtchouk et al (2014), the detailed evolution of the atmosphere is very sensitive to the exact structure of the jet and the initial perturbation, so that our goal here is not to reproduce the results of Polichtchouk & Cho (2012) quantitatively, but instead to show that we obtain the same qualitative evolution of the flow.…”
Section: B1 Baroclinic Instability In An Adiabatic Atmospherementioning
confidence: 52%
See 2 more Smart Citations
“…This is even more so for finite-volume codes such as RAMSES that have problems handling hydrostatic equilibria, and we found that problem to be very helpful in assessing the reliability of our setup. In this appendix, we thus qualitatively reproduce one of the models presented by Polichtchouk & Cho (2012), namely their equatorial jet case, since the base flow is close to the jet configuration we studied here. As noted by Polichtchouk et al (2014), the detailed evolution of the atmosphere is very sensitive to the exact structure of the jet and the initial perturbation, so that our goal here is not to reproduce the results of Polichtchouk & Cho (2012) quantitatively, but instead to show that we obtain the same qualitative evolution of the flow.…”
Section: B1 Baroclinic Instability In An Adiabatic Atmospherementioning
confidence: 52%
“…In this appendix, we thus qualitatively reproduce one of the models presented by Polichtchouk & Cho (2012), namely their equatorial jet case, since the base flow is close to the jet configuration we studied here. As noted by Polichtchouk et al (2014), the detailed evolution of the atmosphere is very sensitive to the exact structure of the jet and the initial perturbation, so that our goal here is not to reproduce the results of Polichtchouk & Cho (2012) quantitatively, but instead to show that we obtain the same qualitative evolution of the flow. Indeed, since we neither use the same equations (Euler vs. primitive) nor the same geometry (Cartesian vs. spherical), a one-to-one quantitative comparison is not possible.…”
Section: B1 Baroclinic Instability In An Adiabatic Atmospherementioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies (e.g., Thrastarson & Cho 2010;Polichtchouk & Cho 2012;Mayne et al 2014;Cho et al 2015) demonstrated that the simulation results might be sensitive to specifications such as forcing and dissipation setup, initial condition, and numerical schemes used in different dynamical cores. In this study, we adopted the MITgcm (Adcroft et al 2004) dynamical core that solves the primitive equations using the finite volume method in a cubesphere grid.…”
Section: Numerical and General Resultsmentioning
confidence: 99%
“…6). Although such instability on Earth and Mars is enhanced by the existence of entropy gradients on the lower surface, several studies have shown that baroclinic instabilities are possible even on gas giants like Jupiter that lack such surfaces (Conrath et al 1981;Read 1988;Williams 2003;Lian & Showman 2008;O'Gorman & Schneider 2008;Polichtchouk & Cho 2012). Typically, such instabilities occur most readily at mid-to high latitudes, where meridional temperature gradients are large and isentropes slope steeply.…”
Section: Background Theory and Prediction Of A Regime Transitionmentioning
confidence: 99%